Approaching First-Line Treatment in Patients With Advanced CMML: Hypomethylating Agents or Cytotoxic Treatment? - Liapis, Konstantinos; Kotsianidis, Ioannis (Frontiers in Oncology, 2021)
Chronic myelomonocytic leukemia (CMML) is a rare clonal haematological malignancy bearing characteristics of both myelodysplastic syndromes and myeloproliferative neoplasms. It primarily affects older people (median age at diagnosis 72 years). There are many challenges encountered in its treatment. One striking issue is the lack of strong clinical evidence from large randomized clinical trials for treating this disease. Another issue is that patients with CMML have highly variable outcomes with current treatments. Additional challenges include a wider application of current knowledge, an improved understanding of pathogenesis, development of new therapies, and management of refractory cases/disease progression. It is clear that there is still progress to be made. Here, we review the available first-line treatment options for advanced CMML. Emphasis has been placed on choosing between hypomethylating agents and cytotoxic treatments, on the basis on disease-specific and patient-specific characteristics. A proper selection between these two treatments could lead to a better quality of care for patients with CMML.